2018
DOI: 10.1016/j.contraception.2018.07.060
|View full text |Cite
|
Sign up to set email alerts
|

There might be blood: a scoping review on women’s responses to contraceptive-induced menstrual bleeding changes

Abstract: Introduction: Concern about side effects and health issues are common reasons for contraceptive non-use or discontinuation. Contraceptive-induced menstrual bleeding changes (CIMBCs) are linked to these concerns. Research on women's responses to CIMBCs has not been mapped or summarized in a systematic scoping review. Methods: We conducted a systematic scoping review of data on women's responses to CIMBCs in peer-reviewed, English-language publications in the last 15 years. Investigator dyads abstracted informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 88 publications
(254 reference statements)
2
26
0
Order By: Relevance
“…Our nding that increased menstrual bleeding was associated with discontinuation aligns with a growing body of literature, highlighting the importance of contraceptive-induced bleeding changes (1,11).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our nding that increased menstrual bleeding was associated with discontinuation aligns with a growing body of literature, highlighting the importance of contraceptive-induced bleeding changes (1,11).…”
Section: Discussionsupporting
confidence: 85%
“…This belief carries profound social consequences and, therefore, may greatly reduce motivation to use contraception (17,39) We did not nd signi cant effects with discontinuation or switching among women who reported less bleeding, although irregular bleeding was shown to reduce the risk of switching. Evidence from qualitative studies in Africa suggests that amenorrhea and irregular bleeding are often viewed negatively and associated with concerns about future fertility, particularly among nulliparous women (11), however recent qualitative evidence in Uganda found that the potential for lighter periods as a side effect of contraception was viewed favorably by women (36). Zimmerman and colleagues found that two-thirds of sexually active women in Uganda strongly agreed that not having a menstrual period as a result of contraceptive use was unhealthy, but agreement was not strongly associated with either discontinuation or switching (Under Review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, fear of health concerns and side effects are top reasons for nonuse of modern contraception among women with unmet need (Staveteig 2016), with particular concern around irregular menstrual cycles (Hindin, McGough, and Adanu 2014; Staveteig 2017). These fears may in turn be linked with perceptions that menstrual changes lead to infertility (Atijosan, Adeyeye, and Ogungbayi 2019; Polis, Hussain, and Berry 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review comprising 100 studies with data on women's responses to contraceptive-induced menstrual bleeding changes concluded that menstrual changes are top reasons for method dissatisfaction, discontinuation, and non-use (25). While the authors point out that substantial variability exists around responses to bleeding changes based on individual experience and social in uence, the importance of contraceptive-induced bleeding changes for women's daily lives and contraceptive satisfaction have been underappreciated by family planning programs and contraceptive product developers.…”
Section: Discussionmentioning
confidence: 99%